Akademisk skriving? For forskarar? - Kåre Johan Mjør (Nordic Journal of Information Literacy in Higher Education)
The Unit for research support at the HVL (Western Norway University of Applied Sciences) library has since the late 2010s offered a series of relatively short introductions to various topics we believe to be useful for researchers, in particular PhD candidates and early career researchers. In addition to “traditional” library topics such as searching, publishing, open science, reference management, databases and other digital resources, we have included sessions on academic writing. The author of this essay has been responsible for these sessions since 2020, and here I will describe more specifically what has been included (and not) within the framework of “academic writing for researchers” and how I understand this topic, that is what I think is particularly relevant for researchers to think about in terms of writing. I will present the theoretical framework I have made use of (in particular Joseph Harris’s book Rewriting) and discuss some examples of academic writing that I find to be productive and informative to discuss. I also take into consideration recent events in the Norwegian public sphere that have created new challenges for us librarians who try to guide academics as writers. The goal of the essay is to contribute to a further reflection on and discussion of what “academic writing for researchers by the library” should be.